Thermal impacts on the early life history of Sauger (Sander canadensis) - Cammack, Daniel L., author; Myrick, Christopher A., advisor; Johnson, Brett M., committee member; Ghalambor, Cameron K., committee member (Colorado State University. Libraries, 2019)
Sauger (Sander canadensis), a large North American member of the family Percidae, often exhibit sporadic recruitment governed by a variety of biotic and abiotic factors. This episodic reproductive success is emblematic in Percids, as it has been documented across a wide geographic area for multiple Percid species. Temperature, the most influential abiotic variable, directly affects Percid recruitment, physiology, and distribution, while simultaneously modifying many other factors that govern population dynamics such as food abundance. The Wind and Bighorn River drainages of Wyoming, among the highest elevation tributaries of the Missouri River basin, remain a stronghold for two native Sauger populations. These populations are among the slowest growing and longest lived in the entire native range and provide an important recreational angling resource. While recent population trends have been positive (2011-2016), conditions in the past decade have resulted in poor recruitment, with only older age classes present in the annual Wyoming Game and Fish Department (WGFD) surveys of the Wind River population (2002-2011). Agency concern over poor recruitment resulted in the initiation of artificial spawning operations in both drainages, with the aim of bolstering these populations. Sauger hatch percentages from these spawning efforts were highly variable, and generally low across all years (0-75%). One hypothesis advanced to explain the observed variable egg survival was that river temperatures leading up to and during the spawn were outside of optimal ranges. Our research explored how temperature affects multiple stages in reproduction including adults, embryos, and prolarvae. Specifically, we tested the effect of temperatures in the range of 10-24°C on the survival and rates of development of Sauger embryos and prolarvae (phase I and II). In the incubation experiment, hatch rates were low for all treatments (<22%). Sauger embryos displayed appreciable thermal plasticity and no differences in hatch percentage were detected in the range of 12.2-18.9°C. Statistically lower hatch rates were detected for our 10°C and diel fluctuating (17-22°C) treatments compared to all others. Hatch timing and duration was inversely related with temperature. We developed a regression model to estimate temperature units (TU's) necessary to reach hatching and duration of hatch (days) based on average temperature. Our results indicate that optimal incubation temperature for Sauger is near 14.5°C. Sauger prolarvae survived at high rates (>90%) to the onset of exogenous feeding in all treatments ≥ 18°C, although pronounced mortality associated with the time that yolk was completely absorbed, suggested that starvation occurred, despite offering brine shrimp (Artemia nauplii) daily. Prolarvae in the 12 and 15°C treatments survived at a statistically lower rate to the onset of exogenous feeding and fed poorly after. We suggest that optimal temperature for prolarvae survival is in the range of 18-24°C with the caveat that rapid mortality can result around the time of yolk absorption if larvae do not successfully feed exogenously. Growth rate (SL) was positively associated with temperature. Time to reach exogenous feeding was negatively associated with average temperature. We developed a regression model predicting TU's necessary for larvae to reach exogenous feeding based on average temperature conditions. We also exposed wild adult Sauger to two pre-spawning temperature treatments, approximately six weeks before the expected spawn date. One treatment was an above average, stochastic thermal scenario (fluctuating), while the other was a gradually warming treatment expected to be near optimal for spawning (control). We evaluated impacts on egg viability, as determined by fertilization and hatch percentages. We also determined egg energy density as a measure of egg quality. We found no differences in fertilization and hatch percentages between treatments, perhaps due to a small sample size (n = 7 spawns). Similarly, there was no difference in mean egg energy density between treatments. Adult mortality was greater in the fluctuating treatment compared to the control (44.4% vs. 26.3%) and females were disproportionately affected. Our research explicitly defines thermal criteria, that will provide managers with guidelines to understand how temperature may influence recruitment in the wild, in addition to providing thermal recommendations for artificial spawning and/or hatchery operations in the future.